A109 Can breaking your wrist break your driving habit?. Issue 2 (June 2015) - Musselwhite, Charles; Calcraft, Melissa; Fox, Rebecca; Swinkels, Annette; Turton, Pat; Young, Sue
Abstract: Background: When someone breaks their wrist and has their forearm in plaster, it presents a disruption to everyday routine, including, often, an enforced change in travel patterns from, for example, driver to passenger, public transport user or walker. This paper investigates changes people make to their travel behaviour addressing how long such changes last, the efficacy of making such changes, emotional responses to the change and whether it has the potential to change behaviour more permanently. It also looks for any differences in individual background and such responses to travel behaviour change. Methods: One hundred and eleven participants (87 female, 24 male; average age 57.08 years) completed a questionnaire as they were having their plaster cast removed following a wrist fracture. The questionnaire addressed their travel behaviour change, driver safety and information provision during their time in plaster (on average of 5-6 weeks). Results: Eighteen percent of participants drove during the time they had a forearm plaster cast on. Risk and affective scales did not predict whether participants drove in a cast, suggesting that practical and utilitarian, rather than psychosocial, reasons were the motivation for driving. Eighty-two percent found other ways of getting around without using their car. Participant's use of buses and trains, walking and taking lifts all increased and overall, across all modes of transport, participants travelled fewer miles but made more journeys. People who changed behaviour reported positive experiences with public transport and with walking, including being able to see parts of the area they had not seen for years and an opportunity for relaxation. Most were able to change their behaviour and still fulfil obligations; in particular all those with jobs were able to reach their place of employment. Yet almost all looked forward to going back to driving as soon as they could, often for the convenience and independence that driving brings. People had to do more planning, had to take longer over journeys and in some cases had to miss regular events, especially discretionary and evening journeys, because of walking or using public transport. Conclusions: Overall, people were able to adapt to a temporary disruption in travel behaviour but more is needed to lock-in such change and maximise positive elements of the change. Journeys are shorter, take longer and need to be planned, all which are seen negatively compared to the convenience of driving.